LEGALITAS PENETAPAN PENGADILAN AGAMA TERHADAP PEMBATALAN PERKAWINAN PASCA MENINGGALNYA ISTRI BERDASARKAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DAN KOMPILASI HUKUM ISLAM (STUDI PENETAPAN NOMOR: 3043/PDT.G/2018/PA.BADG.) - Akmalunnisa, Bunga; Hadiati, Mia (Jurnal Hukum Adigama, 2021)
Cancellation of a marriage is a problem that often occurs in society, but it is different if the Cancellation of a marriage is carried out after the death of one of the prospective bride and groom. In this paper, there are problems that will be discussed, how the legality of the determination of the religious court regarding the Cancellation of a marriage after the death of the wife and how the legal consequences of the legality of the determination of the religious court regarding the Cancellation of a marriage after the death of the wife. The method used in this paper is normative juridical. In terms of the validity of the determination of the Cancellation of a marriage after the death of the wife, the marriage can be annulled, if it does not meet the requirements to carry out the marriage and may result in the termination of husband and wife relations and the termination of inheritance rights because the marriage is considered to have never existed. Therefore, Pasal 92 of the KUHPer, not cancellations in the event of a violation. An annulment claim cannot be accepted if the husband and wife have lived together for three consecutive months, since the husband and wife obtained full freedom and since â€œerror in personaâ€ was found.